2012
DOI: 10.2139/ssrn.1991060
|View full text |Cite
|
Sign up to set email alerts
|

Work Values in Western and Eastern Europe

Abstract: SummaryThe paper reports on work values in Europe. At the country level we find that job satisfaction is related to lower working hours, higher well-being, and a higher GDP per capita. Moving to the micro level, we turn our attention from job satisfaction to analyse empirically work centrality and work value dimensions (without exploring empirically job satisfaction) related to intrinsic and extrinsic values, power and social elements. The results indicate substantial differences between Eastern and Western Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 81 publications
(99 reference statements)
0
7
0
3
Order By: Relevance
“…Borooah 2009, Torgler 2011. However, the two regions involve a large number of countries with different cultural, socioeconomic and labour market conditions, so perceptions of work value and job satisfaction might differ not only between but also within them.…”
Section: Model Specification and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Borooah 2009, Torgler 2011. However, the two regions involve a large number of countries with different cultural, socioeconomic and labour market conditions, so perceptions of work value and job satisfaction might differ not only between but also within them.…”
Section: Model Specification and Methodologymentioning
confidence: 99%
“…Kaiser (2005) with a focus on gender or Origo and Pagani (2008)) or are mainly focused on comparison between the EE and WE regions as a whole. Večerník (2004) and Torgler (2011) analysed work values and found substantial differences between WE and EE. Borooah (2009) showed that the average level of job satisfaction was higher in WE than in EE.…”
mentioning
confidence: 99%
“…Unemployment rates by country and time Generational differences in loyalty may be evident among participating employees in our study given the socio-economic transformation that occurred in the 1990s, and the corresponding changes in workplace environments. Generational differences are clearly evident in work attitudes and work ethic among individuals in former socialist economies (Denisova et al, 2007;Linz and Chu, 2013;Torgler, 2011).…”
Section: Generational Differences In Loyalty?mentioning
confidence: 99%
“…Se ha destacado también una relación directa entre educación y valoración con el empleo, medido con el criterio de satisfacción en el trabajo (Rodríguez-Pose y Vilalta, 2005;Clark, 1996;Long, 2005;Torgler, 2011). Una relación un poco diversificada se percibe cuando los altos niveles educativos orientan la construcción de expectativas laborales, pero esta se encuentra en función de variables de control como la complicación de la labor realizada y los niveles de "inteligencia".…”
Section: Escolaridad Y Centralidad Del Trabajounclassified
“…Diversos estudios han hecho hincapié en señalar que las mujeres valoran en menor medida el trabajo a diferencia de los varones (MOW 1987;Sharabi y Harpaz, 2013) y particularmente decrece la postura en mujeres con hijos(as) (Harpaz y Fu, 1997). Las razones versan en que la continuidad en estilos de vida y condiciones en las que el trabajo no es prioridad para las mujeres hará que las diferencias en centralidad, satisfacción y compromiso laboral sean inferiores comparativamente (Long, 2005;Torgler, 2011).…”
Section: Centralidad Del Trabajo Y Sexounclassified